Different Messages are Transmitted by Individual Duet Contributions and Complete Duets in a Species with Highly Overlapped Duets - Sandoval Vargas, Luis Andrés (2018)
Background: Duet function hypotheses have been mostly studied in bird species that produce duets with male and female solo songs. However, in order to understand if patterns of duet function are similar across all duetting species, it is highly necessary to test the duet function hypotheses in species that produce duets with vocalizations other than solo songs. Objective: We studied the responses of territorial pairs to each sex’s individual duet contribution and complete duets in a species that produces duets with a vocalization other than male and female solo songs. Methods: We conducted a playback experiment where we presented duet contributions of each sex to three populations of White-eared Ground-sparrows (Melozone leucotis) in Costa Rica, during this species’ breeding season in 2016. Results: The responses to complete duets were stronger than those to each sex’s duet contribution, suggesting that complete duets and each sex’s duet contribution have different functions. Complete duets are used to protect resources from intruders (supporting the resource defense hypothesis), and to prevent the partner from being usurped by intruders (supporting the mate-guarding hypothesis). Males used solo songs in response to female duet contributions, and this may work to attract intruder females (increasing the probability of extra-pair copulation). Males also use solo songs in response to male duet contributions, which may work as a signal to repel intruder males and guard their female. In this case, where mate attraction occurs with a completely different type of vocalization than used for duetting, we found a clear pattern of a double agenda for males when a territorial intrusion occurs. Conclusions: This study provides strong support for the dual function hypothesis in duets and reveals conflicting selective pressures between pair members relative to each hypothesis.